Recent Perspectives on Trade and Inequality - Harrison, Ann; McLaren, John; McMillan, Margaret (World Bank, Washington, DC, 2012)
The 1990's dealt a blow to traditional Heckscher-Ohlin analysis of the relationship between trade and income inequality, as it became clear that rising inequality in low-income countries and other features of the data were inconsistent with that model. As a result, economists moved away from trade as a plausible explanation for rising income inequality. In recent years, however, a number of new mechanisms have been explored through which trade can affect(and usually increase) income inequality. These include within-industry effects due to heterogeneous?firms; effects of offshoring of tasks; effects on incomplete contracting; and effects of labor-market frictions. A number these mechanisms have received substantial empirical support.